PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ANDROID MENGGUNAKAN ARTICULATE STORYLINE 3 PADA MATERI HIMPUNAN KELAS VIII SMP NEGERI 2 WOTU - Ferawati Jusri; Irma T; Lisa Aditya Dwiwansyah Musa; Sumardin Raupu (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2026)
This study aimed to develop an Android-based interactive learning media using Articulate Storyline 3 for the topic of sets for eighth-grade students at SMP Negeri 2 Wotu. The study was motivated by the limited educational facilities and infrastructure available at the school, the predominance of conventional teaching approaches, and the lack of teachers' creativity in utilizing instructional media, which caused students to feel bored during the learning process. Therefore, this research sought to develop an interactive Android-based learning media to enhance students' engagement and learning outcomes in mathematics. This research employed the Research and Development (R&D) method using the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The participants were 28 eighth-grade students of SMP Negeri 2 Wotu. Data were collected through interviews, observations, validation sheets, questionnaires, and learning achievement tests. The results indicated that the developed learning media met the criteria of validity, practicality, and effectiveness. The validation results from both material experts and media experts showed that the product was categorized as highly valid. The practicality test conducted by teachers and students demonstrated that the media was highly practical. Furthermore, the effectiveness test revealed that the media significantly improved students' mathematics learning outcomes. Therefore, the Android-based interactive learning media developed using Articulate Storyline 3 is considered feasible and effective for use in mathematics learning, particularly on the topic of sets.